IOT-BASED SMART BUILDING MANAGEMENT: A DUAL APPROACH TO AUTOMATION AND SAFETY WITH REAL-TIME MONITORING AND ALERTS - Muhammad Danyal Khan,; Haq Nawaz,; Muhammad Jawad Khan,; Osama Turk,; Navaid Ali,; Aftab Ahmed Soomro,; Basit Ahmad, (Spectrum of Engineering Sciences, 2025)
The integration of Internet of Things (IoT) technologies into building management systems has revolutionized the development of smarter, more efficient, and safer environments. This paper presents a dual approach to smart building management, emphasizing both automation and safety through real-time monitoring and alert mechanisms. The automation system utilizes bi-directional ultrasonic sensors to monitor building occupancy, and, in conjunction with temperature sensors, dynamically adjusts appliances such as lights, fans, air conditioners, and heaters to optimize comfort and energy efficiency. A notable feature of the system is its ability to enable remote monitoring and control of appliances via SMS communication. On the safety front, the system incorporates a suite of IoT sensors including smoke, flame, gas, temperature, and ultrasonic sensors to detect hazards such as fires or gas leaks. In response to such events, the system automatically disconnects circuit breakers, activates alarms for evacuation, and dispatches real-time alert messages to occupants’ mobile devices. This dual- function system enhances operational efficiency, reduces energy consumption, and significantly improves building safety. The paper details the design, implementation, and practical benefits of this integrated IoT-based smart building management solution.